Effects of muscle strength and endurance on blood pressure and related cardiometabolic risk factors from childhood to adolescence - Demmer, D.; Beilin, L.; Hands, B.; Burrows, S.; Cox, K.; Straker, Leon; Mori, T. (Lippincott Williams & Wilkins, 2016)
Objective: This study aimed to examine the evolution of relationships between measures of muscle strength and endurance with individual cardiometabolic risk factors from childhood to late adolescence in a prospective population-based cohort. Methods: Participants from the Western Australian Pregnancy Cohort (Raine) Study at ages 10, 14 and 17 were analysed, using longitudinal linear mixed model analyses. Results: Handgrip strength after adjusting for the confounding effects of BMI was positively associated with SBP, but not DBP. The association between handgrip strength and SBP was stronger in men than women at all time points [coefficient (women): 0.18, P < 0.001; sex × handgrip strength coefficient: 0.09, P = 0.002]. The association was strongest at 10 years and significantly attenuated over time (year × handgrip coefficient from 10 to 14 years: −0.11, P = 0.003; year × handgrip coefficient from 10 to 17 years: −0.19, P ≤ 0.001). After the inclusion of BMI as a confounder, handgrip strength was significantly negatively associated with homeostatic model assessment of insulin resistance and high-sensitivity C-reactive protein over time in both sexes. Back muscle endurance was positively associated with SBP, but not DBP, after adjustment for the confounding effects of BMI (coefficient: 0.01, P = 0.002). There were small, albeit significant, inverse associations between back muscle endurance and log homeostatic model assessment of insulin resistance and log high-sensitivity C-reactive protein. Conclusion: The positive association between handgrip strength and back muscle endurance with SBP throughout childhood and adolescence contrasts with beneficial effects on other related traditional cardiometabolic risk factors. Mechanisms underlying these paradoxical effects on SBP warrant further investigation.